Using soft systems methodology to align community projects with sustainability development in higher education stakeholders' networks in a Brazilian university - Paucar-Caceres, Alberto (2021)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPN por restricciones de la casa editorial donde ha sido publicado.